Penenggulangan Caplak Rhipicephalus sanguineus dengan Vaksinasi - Tutuk Astyawati; Retno Wulansari (Institut Pertanian Bogor, 2008)
The tiltle of this study is Rltipiceplta/us sanguineus controls by vaccination. The vaccine used from crude adulttick extracts to vaccinated dogs, shccps and rabits. The experimental animals were inoculated subkutaneously, threetimes every two weeks with crude adult tick extracts and adjuvant. Fifteen days after the last inoculation all animalswere submitted to challenge infestation with unfed adult ticks. The dogs were placed in the severe contaminatedenvironment. The ticl.:s were placed inside a feeding chamber consisting of a plastic tube to the saved back of shccps.Ticks were placed for save behind the ear of rabbits. Observation was done 3 days after infestation. The results ofthis investigation were observed that most of ticks were recovered in dogs either vaccinated or non vaccinatedgroups, however on the control groups without vaccinated ticks the infestation were higher than vaccinated groupsas well as in the sheeps and rabbits. In the rabbits although ERCE value between vaccinated and non vaccinatedgroups not significants statistically, there were demonstrated that ERCE value in the vaccinated groups lower thancontrol groups without vaccinated. According to our investigation we can concluded the usc of tick antigen couldinduced resistance by direct immunisation. Adult ticks of Rltipicepltalus sanguineus crude extract tends to induceresistance in rabbits, sheeps and dogs with different level of resistance. The immunity seems not to be acquiredduring a natural exposure tends to evolved with crude adult tick extracts vaccinations.Keywords: resistance, rhipicephalus, sanguincus, vaccination